2005
DOI: 10.1175/jas3386.1
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Spectral Measurements of Ocean Directional Reflectance

Abstract: The Cloud Absorption Radiometer (CAR) was flown aboard the University of Washington Convair 580 (CV-580) research aircraft during the Chesapeake Lighthouse and Aircraft Measurements for Satellites (CLAMS) field campaign and obtained measurements of bidirectional reflectance distribution function (BRDF) of the ocean in July and August 2001 under different illumination conditions with solar zenith angles ranging from 15° to 46°. The BRDF measurements were accompanied by concurrent measurements of atmospheric aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…This difference in response at lower wind speed is reminiscent of Wu's reanalysis of the Cox and Munk data (Equation 18). The study of Gatebe et al [51], using data from airborne instruments for coastal and deep waters in the western Atlantic Ocean, found that the Cox and Munk model fitted their data well for most conditions, but underestimated the maximum glint for wind speeds below 3 m/s.…”
Section: The Cox and Munk Statistical Model Of The Sea Surface Statementioning
confidence: 97%
“…This difference in response at lower wind speed is reminiscent of Wu's reanalysis of the Cox and Munk data (Equation 18). The study of Gatebe et al [51], using data from airborne instruments for coastal and deep waters in the western Atlantic Ocean, found that the Cox and Munk model fitted their data well for most conditions, but underestimated the maximum glint for wind speeds below 3 m/s.…”
Section: The Cox and Munk Statistical Model Of The Sea Surface Statementioning
confidence: 97%
“…For instance, the NASA airborne data will additionally be presented, which have been obtained below a cloud layer by aircraft flights at an altitude around 350 m at South Africa (20.0-21.7 • S, 13.0-13.7 • E) (Gatebe et al 2003;Genya et al, 2011). These observations were made in eight spectral channels, 340, 381, 472, 682, 870, 1.035, 1.219, and 1.273 nm, with the Cloud Absorption Radiometer (CAR) (King, 1987;King et al, 1990King et al, , 1996Gatebe et al 2003Gatebe et al , 2005.…”
Section: Experimental Campaign and Equipmentmentioning
confidence: 99%
“…The observed reflectance patterns show peak values of sun glint near the specular direction. Gatebe et al (2005) compare these observations, under a variety of wind conditions, to traditional model simulations. Spectral and broadband radiative fluxes measured from COVE are shown in Figs.…”
Section: Experiments Summary and Key Resultsmentioning
confidence: 99%
“…The CV-580 also deployed several radiometric instruments to measure spectral and broadband shortwave radiation, including the 14-channel NASA AMES King et al 1986). The AATS-14 provided continuous measurements of aerosol optical depth, while the CAR provided the important lower boundary condition (BRDF) (Gatebe et al 2005), both critical for radiative closure studies and validation of AOD derived from Terra and ER-2 airborne data. Although the CAR measurements are limited to the wind and sea conditions and solar geometries encountered during CLAMS, they will be useful for checking the validity of the long-term measure- (Su et al 2002).…”
Section: Aircraftmentioning
confidence: 99%